2023
DOI: 10.12659/aot.938287
|View full text |Cite
|
Sign up to set email alerts
|

Detecting Donor-Derived DNA by Real-Time PCR in Recipients Suspected of Graft-Versus-Host-Diseases After Liver Transplantation: A Case Series and Literature Review

Abstract: Background Graft-versus-host disease (GVHD) after liver transplantation (LT) is a rare but fatal complication. GVHD diagnosis is usually based on clinical symptoms and pathologic confirmation. However, it is often misdiagnosed due to its non-specific symptoms. Here, we report the detection of donor-cell chimerism using peripheral blood (PB) donor-derived deoxyribonucleic acid (ddDNA) for 3 cases with suspected GVHD after LT (GVHD-LT) through real-time quantitative polymerase chain reaction (qPCR) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…GvHD occurs due to recognition of host antigens as foreign by immunocompetent T cells in the graft, followed by extensive tissue damage and life-threatening complications. A pilot study by Ha et al [ 23 ] showed the promising role of early detection of donor cell chimerism using peripheral blood donor-derived DNA through real-time PCR reaction targeting 39 insertion and/or deletions of chromosomes to halt fatal progression of GvHD after liver grafting.…”
Section: Liver Transplantationmentioning
confidence: 99%
“…GvHD occurs due to recognition of host antigens as foreign by immunocompetent T cells in the graft, followed by extensive tissue damage and life-threatening complications. A pilot study by Ha et al [ 23 ] showed the promising role of early detection of donor cell chimerism using peripheral blood donor-derived DNA through real-time PCR reaction targeting 39 insertion and/or deletions of chromosomes to halt fatal progression of GvHD after liver grafting.…”
Section: Liver Transplantationmentioning
confidence: 99%